Alpha1-fetoprotein in the diagnosis of hepatoma: statistical and cost benefit aspects. Issue 12 (December 1977) - Phillips, P J; Rowland, R; Reid, D P; Coles, M E
Abstract : A rational comparison of different serum concentrations of alpha1-fetoprotein (S-AFP) in the diagnosis of hepatoma must be made. We took data on the sensitivity and specificity of different diagnostic S-AFP concentrations from the literature and evaluated them statistically and by Bayesian analysis. In our patients (hepatoma prevalence 0.028) a sensitive diagnostic concentration (30-50 ng/ml) will misdiagnose hepatoma so often that a positive test will indicate hepatoma in only 10% of cases. A positive test at a specific diagnostic concentration (500 ng/ml) indicates hepatoma in 100% of cases and is preferable in terms of cost benefit. Although the lower concentration will diagnose a larger proportion of patients with hepatoma (74% compared with 59%) the 'costs' of excluding false positives are considerable (A$2545 per extra case with 2.5% of patients suffering significant morbidity). In western societies, where the prevalence of hepatoma is low, a higher, less sensitive but more specific diagnostic S-AFP concentration is appropriate.